Global prevalence and molecular epidemiology of mcr-mediated colistin resistance in Escherichia coli clinical isolates: a systematic review - Dadashi, Masoud; Sameni, Fatemeh; Bostanshirin, Nazila; Yaslianifard, Somayeh; Khosravi-Dehaghi, Nafiseh; Nasiri, Mohammad Javad; Goudarzi, Mehdi; Hashemi, Ali; Hajikhani, Bahareh (Journal of Global Antimicrobial Resistance, 2022)
•Molecular epidemiology of mcr-mediated colistin resistance in Escherichia coli clinical isolates.•Prevalence of colistin-resistant E. coli isolated from clinical samples in different continents.•Prevalence of colistin-resistant E. coli isolates in different countries.•Distribution of sequence types (STs) among colistin-resistant E. coli in different continents.•Distribution of STs among colistin-resistant E. coli isolates in different countries. The continuing rise in infections caused by multidrug-resistant (MDR) bacteria is one of the most serious public-health issues in society today. Colistin is a last-resort antimicrobial drug used to treat infections caused by MDR Gram-negative bacteria, therefore resistance to this antibiotic is extremely hazardous. The current study aimed to evaluate the global prevalence nd distribution of colistin resistance genes among human clinical isolates of Escherichia coli by systematic review. PubMed, Embase and Web of Science databases were systematically searched. For further evaluation, all original English language articles that reported colistin resistance in E. coli clinical isolates published between 2000 and 2020 were examined. Of 4857 initial articles, after various stages of review and evaluation 190 related articles were selected for the systematic review. More than 79% of the publications selected in this research were published from 2014–2020. In Asia, Europe, America, Africa and Oceania, the prevalence of mobile colistin resistance (mcr)-harbouring colistin-resistant E. coli was 66.72%, 25.49%, 5.19%, 2.27% and 0.32 %, respectively. The recent widespread dissemination of E. coli strains harbouring mcr genes conferring colistin resistance, especially in Asia and Europe, is concerning and requires more attention.